Reasons not to select patients for corneal refractive surgery - Ribeiro,André Luiz Parolin (2002)
Purpose: To present how the section of Refractive Surgery of the Federal University of São Paulo assesses the candidates and the reasons to indicate for corneal refractive surgery. Methods: We examined 1626 patients. Anamnesis, complete ophthalmologic examination and corneal topography were performed in all patients. The patients spontaneously seeked evaluation at the Refractive Surgery Section by telephone without a previous screening. Reasons to refuse patients for refractive surgery were previously established by the Refractive Surgery Section. Results: Based on current technology and clinical experience, 265 patients (16.29%) were refused for excimer laser corneal refractive surgery. Myopia of patients who had insufficient preoperative corneal pachymetry for the laser treatment was the main cause for refusal (51 patients). Cataract (45 patients), keratoconus (31 patients), amblyopia (21 patients), hyperopia > 5 diopters and mixed astigmatism (19 patients), presbyopia (unaware ness of the need for optical correction after the procedure; 16 patients), pupillary diameter > 5mm (9 patients), single eye (9 patients), progressive myopia (8 patients), postradial keratotomy (7 patients) and low ametropia (7 patients) were among the reasons for the refusal. Conclusion: Candidates for excimer laser corneal refractive surgery may present risk factors that should be known in order to avoid complications.